A rare case of gas under diaphragm due to spontaneous perforation of uterus due to gas gangrene of uterus with clostridium perfringens infection presenting as intestinal perforation - Harika, D. Navya Sesha; Rao, T. Uma Maheswara; Sireesha, P.; Jithendra, D.; Pandu, Satya Sundeep (International Surgery Journal, 2019)
Uterine perforation is an uncommon, perforation due to clostridium perfringens is very rare, but potentially serious complication of uterine gangrene is due to clostridial infection, uterine manipulation, evacuation of retained products, termination of pregnancy, during coil insertion and hysteroscopic procedures. We report a 60 year old female patient presented with abdominal pain, constipation and Fever with features of septic shock. X-ray showed free gas under both domes of diaphragm. CT showed gas under diaphragm and hollow viscus perforation. This report aims to alert surgeons to the possibility that perforation of uterus due to gangrene with clostridium perfringens infection also shows air under diaphragm apart from routine causes. Correct diagnosis and treatment is essential for the survival of the patients with gas under diaphragm due to gas gangrene of uterus.